Analysis of the dynamics of physical development and functional state of 9-12- year-old schoolchildren playing volleyball - Trofimenko, Vira; Romanyshyna, Oksana; Anichkina, Olena; Ivanchuk, Maria; Богданюк, Антоніна; Zoriy, Yaroslav; Moseichuk, Yurii; Koshura, Andrii; Yarmak, Olena; Galan, Yaroslav (Editura Universitatea din Pitesti, 2019)
The article reviews the dynamics of physical development and the functional state of the cardiovascular system of schoolchildren aging from 9 to 12 years, who play volleyball during their extracurricular time. The aim of the research is to identify the peculiarities of influence of volleyball practice on the body of boys and girls aged 9-12 years. Materials and methods: analysis of scientific and methodological literature, generalization of best educational experience, anthropometric methods, physiological methods, methods of mathematical statistics. Altogether 99 pupils (n=99) were involved in the research, including 49 girls and 50 boys aged 9-12 years. The study was carried out on the basis of secondary schools of the city of Chernivtsi schools № 6, 27. Volleyball classes were held 3 times a week. The length of a training session was 2 hours. Results: it has been analysed the age dynamics of the morpho-functional state of pupils playing volleyball. Analysis of the results of the research made it possible to supplement the knowledge in the field of age morphology and physiology on the growth rates and development of the child population aging from 9 to12 years. The research found out that the indicators of body length in the girls aged 9-12 years are higher than in the boys of this age group, and the indicators of body weight, on the contrary, are larger in boys. The total increase in the body length in the girls from 9 to 12 years is 14.3 cm, in boys, - 16.5 cm. For 4 years, the body mass index in girls increased by 11.7 kg, in boys - by 10.7 kg. It should be pointed out that there was no statistically significant difference (p> 0.05) in the indicators of body length and body weight, dynamometry of the right and left hands, heart rate at rest, systolic blood pressure and Ruffier index between girls and boys aged from 9 to 12 years. A statistically significant difference (p <0.05) is observed between the boys and girls aged from 9 to 12 years in the indicators of chest girth, inspiratory and expiratory chest girth. And also a statistically significant difference (p <0.05) is observed between boys and girls of 9 years of age in the diastolic blood pressure indicator. Conclusion: it was established that volleyball training sessions have a positive effect on the development of the growth processes of the student population, improve functioning of the cardiovascular system.
Аналіз динаміки фізичного розвитку та функціонального стану 9-12- річних школярів, які грають у волейбол
У статті розглянуто динаміку фізичного розвитку та функціонального стану серцево-судинної системи. Система 9-12-річних школярів старіє під час позаурочного часу гри у волейбол. Мета дослідження полягає у виявленні особливостей впливу практики волейболу на тіло хлопчиків і дівчаток у віці 9-12 років. Матеріали та методи: аналіз наукової та методичної літератури, узагальнення кращих освітніх досвідів, антропометричні методи, фізіологічні методи, методи математичного статистики. Всього в дослідженні було задіяно 99 учнів (n = 99), у тому числі 49 дівчат і 50 хлопчиків у віці 9-12 років років. Дослідження проводилося на базі загальноосвітніх шкіл міста Чернівців загальноосвітньої школи № 6, 27. Заняття з волейболу проводилися 3 рази на тиждень. Тривалість тренування склала 2 години. Результати: було проаналізовано вікову динаміку морфо-функціонального стану учнів, що грають у волейбол. Аналіз результатів дослідження дало можливість доповнити знання в області вікової морфології та фізіології; темпи зростання і розвиток дитей віком від 9 до 12 років. Дослідження показало, що показники довжини тіла у дівчаток у віці 9-12 років вище, ніж у хлопчиків цієї вікової групи, а показники маси тіла, навпаки, більші у хлопчиків. Загальне збільшення довжини тіла у дівчаток від 9 до 12 років - 14,3 см, у хлопчиків - 16,5 см. За 4 роки індекс маси тіла у дівчаток збільшився на 11,7 кг, у хлопчиків - на 10,7 кг. Слід зазначити, що статистично значущої різниці (p> 0,05) у ньому не було. Показники довжини тіла та маси тіла, динамометрія правої та лівої рук, частота серцевих скорочень у спокої, систолічний артеріальний тиск і індекс Руф'є між дівчатами і хлопчиками у віці від 9 до 12 років статистично значуще. Різниця (р <0,05) спостерігається між хлопчиками і дівчатками у віці від 9 до 12 років за показниками грудної клітки обхват, надихання і видих грудей. Також спостерігається статистично значуща різниця (р <0,05) між хлопчиками і дівчатками у віці 9 років за показниками діастолічного артеріального тиску. Висновок: заняття з волейболу позитивно впливають на розвиток процесів росту студента популяції, поліпшення функціонування серцево-судинної системи.
Keywords: physical development;functional state;schoolchildren;volleyball;фізичний розвиток;функціональний стан;школярі;волейбол